Rethinking Love as Union: "As if our boundaries were melting... - Losoncz, Mark (Problems / Problemos, 2024)
This article reconsiders one of the most important theories of romantic love in contemporary philosophy, the theory of love as union. Drawing on observations from transpersonal research, the article raises the question whether it is not worthwhile to accept, at least partially, a strong sense of union in the context of love. Thus the article takes a position that is not taken by anyone in contemporary philosophy. In this context, the article also briefly analyses one of the most important variants of love as union, a union with God. At the end, the suggestion is made that it makes more sense to talk about connections rather than relations in the case of fulfilled love.